Circulating levels of prolactin are elevated in patients with rheumatoid arthritis: a meta-analysis. Issue 2 (17th February 2019) - Wu, Qian; Dan, Yi-Lin; Zhao, Chan-Na; Mao, Yan-Mei; Liu, Li-Na; Li, Xiao-Mei; Wang, De-Guang; Pan, Hai-Feng
ABSTRACT: Background : Prolactin (PRL), an inflammatory hormone with cytokine properties, has long been proposed to play a crucial role in the pathogenesis of autoimmune disorders, including rheumatoid arthritis (RA). However, the circulating levels of PRL in RA were discordant among published studies. Methods : PubMed, Embase, and The Cochrane Library database were systematically searched from inception up to 30 June 2018. The available studies were obtained from the initial search in accordance with the rigorous inclusion and exclusion criteria. Relevant data from the included literatures were extracted. Methodological quality was evaluated in order to refine the final search results. All statistical analyses were conducted using software STATA version 12.0. Results : Of 698 articles were yielded for eligibility, a finally analysis involving 628 RA cases and 430 controls from 14 published studies were included. When compared to healthy controls, there was a significantly higher level of circulating PRL in patients with RA with a pooled SMD of 1.08 (95% CI = 0.41 to 1.74, P < 0.001), particularly in Asians, age ≥50, enzyme-linked immunosorbent assay (ELISA) group and subjects with erythrocyte sedimentation rate (ESR) ≥25 mm/h. Conclusions : Our meta-analysis demonstrates a significantly higher level of circulating PRL in RA patients when compared to healthy controls, and it was associated with region, age, measurement type and ESR.